Is it safe enough? A pilot feasibility study of an 8-day intensive treatment for severe PTSD - Gahnfelt, Hannes; Carlsson, Per F. G.; Blomdahl, Christina (Frontiers in Psychiatry, 2023)
Intensive treatments for posttraumatic stress disorder (PTSD) are gaining increased research support. Treatment models targeting Complex PTSD and previously treatment-resistant PTSD have shown a good effect. A pilot study was performed to assess the feasibility of an 8-day intensive treatment program for severe PTSD in a Swedish public healthcare setting. Eleven participants completed treatment, and overall, the reduction in PTSD symptoms was considerable. Also, loss of diagnosis at 3-month follow-up was 100%. No adverse events occurred, and no elevation of suicidal intentions was reported. Symptom exacerbation could not be observed in the data and dropout due to the intensity of the treatment format did not occur. Based on these positive results, it is recommended that further research with larger samples is conducted. If found safe and effective, the 8-day treatment program could be an important addition to psychiatric healthcare.